IDENTIFIKASI PENYEBAB RISIKO KETERLAMBATAN PROYEK KONSTRUKSI BANGUNAN GEDUNG TINGGI HUNUIAN (STUDI KASUS : PROYEK PEMBANGUNAN CONDOTEL DAN APARTEMEN BHUVANA RESORT CIAWI, BOGOR) - Retna Kristiana; Hermawan Prasetyo (Sekolah Tinggi Teknik - PLN, 2017)
The construction project of the building is said to be one of the high-risk projects given the weight of workand the high structures to be built. The possibility of constraints during implementation of the project couldresult from resources that do not fit, the constraints of tools and materials, methods and poor management, aswell as nature and the environment that is difficult predict. Then affects the performance time, causing delaysin construction and project work directly detrimental to the owner of the Project and Konstraktor. InAvoiding the risk of delays, it is necessary to study on the risks of the construction of buildings.By usingquantitative descriptive method, through a questionnaire based on 30 respondents, then the data results of thequestionnaire will be tested instrument using SPSS version 24 and in the analysis based on the PMBOK.Anlisis of the results and findings of the dominant risk in the project Bhuvana Resort Ciawi, then do a riskresponse is based on the advice of experts to address the risks in order to improve the performance time.